Comparative study of hemostasis file in newly diagnosed leukemia patients and healthy persons at the Hematology and Blood Transfusion Department, National Hospital, Abuja - Nuhu Andrew Yashim; Dorcas Yetunde Obazee; Olumide Faith Ajani; Paul Olaiya Abiodun; Love Adeiye Ajani; Felix Olaniyi Sanni (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Hemostasis is a complicated and multifaceted condition that often leads to the stoppage of bleeding from injuries. At presentation, blood coagulation irregularities are common in patients with acute leukemia. AIM AND OBJECTIVE: This study aimed to compare hemostasis profiles of newly diagnosed leukemia patients with healthy persons. METHODOLOGY: This is a cross-sectional study carried out at the Hematology and Blood Transfusion Department of the National Hospital Abuja, Nigeria, from June 2018 and May 2020 among 30 newly diagnosed leukemia patients and 30 healthy persons. Complete blood counts, platelets, hemoglobin, total white blood count, packed cell volume prothrombin time (PT), activated partial thromboplastin time (APTT), erythrocyte sedimentation rate (ESR), and fibrinogen were assayed on patients' venous blood using the standard methods. Data analysis was done using software IBM-SPSS version 25. Associations between the variables were determined using Student's t-test taking a P < 0.05 as significant. RESULTS: The mean and median age of the leukemia patients was 45.8 ± 10.73 and 41 years, respectively. The mean value of PT (21.2 ± 0.9 seconds) and APTT (39.0 ± 1.4 seconds) was raised significantly (P < 0.001) in leukemia patients than in control (4.8 ± 0.3 s) and (13.9 ± 0.3 s). The mean value of ESR among leukemia patient was 41.7 ± 4.6 mm/h, while it was 29.6 ± 0.4 mm/h in control (P < 0.001). Mean value of fibrinogen reduced significantly 181.9 ± 3.70 mg/dl in leukemia patients as compared to control 261.6 ± 5.21 mg/dl (P < 0.001). CONCLUSION: This study found significant differences in hematological and hemostasis profiles levels between leukemia and healthy persons, which shows the presence of inflammation.